2003
DOI: 10.1046/j.1445-2197.2003.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of adhesive surgical tape with the absorbable continuous subcuticular suture

Abstract: There is no evidence in the scientific literature to justify or support the practice of closing a surgical wound with both subcuticular suture and adhesive surgical tape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Adhesive tapes are used most frequently as adjunctive wound support after staples or sutures are removed, in conjunction with buried dermal sutures, or with absorbable running subcuticular sutures in low-tension wounds. [19] Applying the surgical adhesive tapes in a parallel, non-overlapping fashion after coating the entire application area with adjuvant adhesive is the optimal application technique that provided the best adherence over time. [19] There are many important factors in tape application, including dry skin, accurate apposition of edges, strict homeostasis, and the use of an adhesive adjunct; in addition, the tension should be distributed along the entire tape to prevent blisters [Table 2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adhesive tapes are used most frequently as adjunctive wound support after staples or sutures are removed, in conjunction with buried dermal sutures, or with absorbable running subcuticular sutures in low-tension wounds. [19] Applying the surgical adhesive tapes in a parallel, non-overlapping fashion after coating the entire application area with adjuvant adhesive is the optimal application technique that provided the best adherence over time. [19] There are many important factors in tape application, including dry skin, accurate apposition of edges, strict homeostasis, and the use of an adhesive adjunct; in addition, the tension should be distributed along the entire tape to prevent blisters [Table 2].…”
Section: Discussionmentioning
confidence: 99%
“…[17] Microporous strips allow the passage of gas and water from the skin surface, which make the environment unsuitable for bacterial proliferation and therefore lead to less wound infections. [19] Carpendale et al ., and Marples et al ., demonstrated that wounds closed with skin tapes were resistant to infection. [2122] In addition, Conolly et al ., reported a lower rate of infection for taped wounds (3.8% vs. 14% for sutured wounds) in patients with clean contaminated wounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations